A study of endocrine profile in premenopausal women with hirsutism - J Lakhani Som; J Lakhani Om; R C Raval (Journal of Integrated Health Sciences)
Background The aim of the study was to find the endocrinal profile of patients with hirsutism presenting to dermatology OPD. Hirsutism is defined objectively by Modified Ferriman-Gallwey score ≥ 8 (mFG). Methods The study included 44 premenopausal women in whom after history and clinical examination, endocrine tests were done which included Diabetes profile, TSH, FSH, LH, Free and Total Testosterone, DHEAS, Fasting insulin,17-hydroxyprogesterone and Prolactin. Results Mean age of the patients was 20-29 years while duration of symptoms was of 3 years. Upper lip was the most common site for hair growth while upper arm was the least common. Hair loss and menstrual irregularity were common associated findings. Obesity had a significant correlation with severity of hirsutism. Mean total testosterone in study patients was 64.31 ng/dl. There was no correlation between severity of hirsutism and any of the endocrinal tests. Idiopathic hirsutism (IH) was the most common diagnosis, closely followed by PCOS. We detected 1 case of Non classical Congenital Adrenal Hyperplasia and no cases of Ovarian or Adrenal tumors. Serum testosterone and LH/FSH ratio were significantly elevated in PCOS group as compared to IH group. Conclusion Obesity had a strong relation with severity of Hirsutism independent of other parameters. Fasting blood sugar, serum testosterone, TSH and Fasting insulin levels had no correlation with severity of Hirsutism.